Gut microbial diversity in Apis cerana indica and Apis florea colonies: a comparative study - Khan, Khalid Ali; Ganeshprasad, D. N.; Sachin, H. R.; Shouche, Yogesh S.; Ghramh, Hamed A.; Sneharani, A. H. (Frontiers in Veterinary Science, 2023)
Introduction: The significance of gut microbiota in honey bee health, nutrition, host-symbiont interaction and considering its potential as a research model, gut symbiont evolution and ecology has been emphasized by recent discoveries of significant strain-level variation, protective and nutritive capabilities, and disease-related disruptions to the microbial community. Many regions of Asia and Africa are inhabited by the dwarf honey bee, Apis florea. It naturally pollinates more than 35 crops in its habitat. Studying its microflora and potential for pollination is therefore of foremost importance. Methods: In the present investigation, we aimed to explore the gut bacteriobiome composition of two distinct honey bee species, Apis florea and Apis cerana indica using high throughput sequencing. The phylum Proteobacteria dominated the bacterial community in both A. cerana indica (50.1%) and A. florea (86.7%), followed by Firmicutes (26.29% and 12.81%), Bacteroidetes (23.19% and 0.04%) and Actinobacteria (0.4% and 0.02%) respectively. The gut bacteria of A. cerana indica was more diverse than that of A. florea. Results and Discussion: The observed variations in bacterial genomic diversity among these critical pollinator species may have been influenced by the apiary management techniques, ecological adaptation factors or habitat size. These variations can have a significant effect on host-symbiont interactions and functioning of gut microbiota highlighting the importance of metagenomic survey in understanding microbial community ecology and evolution. This is the first comparative study on variation in bacterial diversity between two Asian honey bees.